Unmet needs for family planning in a municipal area in North Kerala, India - MM, Jesha; NM, Sebastian; Haveri, Sheela P.; Nath, Arya S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: An important concept to describe effectiveness of family planning programme is unmet need for family planning. Most married women want to limit childbirth and space deliveries but many are unable use contraceptives for varying reasons leading to unmet need. According to national survey in India (NFHS 3), the total unmet need is 13.2% (unmet need for spacing- 6% and limiting- 7%). According to district survey (DLHS 3), in Malappuram district, Kerala, India, the total unmet need was 19.7% (11.4% for spacing and 8.3% for limiting) higher than national unmet need. The objective of this study was to find out unmet need for family planning and its causes and the contraceptive practices among married women of reproductive age group (15-49 years) in Perinthalmanna municipality in northern Kerala, India. Methods: A cross sectional study was conducted in 35 wards of Perinthalmanna municipality between 8 April to 6 June 2015. The sample size was calculated as 725. From each of the 35 wards, 21 houses were selected randomly and married women in the reproductive age group 15-49 were interviewed using a semi structured questionnaire. Data was analyzed using epi- info version 7. Results: Among the 753 married women, the total unmet need was 21.2% (spacing 16.9, limiting 4.3). Among 87 (11.6%) currently pregnant women, 66 wanted to conceive, 20 wanted to delay and one didn’t want at all. Among the 666 non-pregnant women, 69 were considered in fecund. Among 326 (48.94%) contraceptive users 26.9% had undergone sterilization; 47.5% were using copper T; 13.5% used condoms and 11.9% used oral pills. Out of 340 non pregnant women not currently using any contraceptives, 24% did not want to conceive ever; 27% wants to conceive but later and 38.8% were ready to conceive now. Fear of complications, considering it against religious faith, lack of knowledge and partner’s opposition were common reasons for not using contraception. Conclusions: The unmet need for Family Planning is high and in order to reduce the gap, the program should address the above reasons.